Strategi Pemetaan Genangan Banjir Sungai di Kota Pekalongan Menggunakan Model SCS-CN - Az Zahra, Talitha; Abdulharis, Rizqi; Nurmaulia, Sella Lestari; Julian, Miga Magenika (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2023)
Pekalongan City consistently experiences annual floods. In this research, we aimed to map the distribution of potential flood inundation in Pekalongan City under two scenarios: the existing land cover and urban planning (Rencana Tata Ruang Wilayah/RTRW). We utilized hydrological modeling to assess the suitability of the RTRW for future implementation. The Soil Conservation Service – Curve Number (SCS-CN) method was employed, incorporating Digital Elevation Model (DEM) data, soil data, precipitation data, and two sets of land cover data (existing and urban planning). The findings indicate that under the existing land cover, approximately 13.97% of the area is susceptible to flooding, while the remaining 86.03% is not at risk. Conversely, the model using the urban planning (RTRW) scenario suggests that 14.06% of the area has the potential to flood, while 85.94% is not susceptible to flooding. The increase in potential flooding in the urban planning scenario may be attributed to the expansion of residential areas and the reduction of plantation and dry land cover. Furthermore, in assessing monthly modeling results, we observed that the area with flood potential is highest in December 2022 and lowest in June 2022. Considering topographical conditions (DEM), we found that the potential for flood inundation is fairly and evenly distributed in flat areas, mostly with elevations of less than 11 meters. Areas at higher elevations are predominantly free from flood potential, but it is noteworthy that certain areas in the Pekalongan Selatan District, with elevations higher than 11 meters, still have the potential for flooding. Keywords: Flood, hydrology model, SCS-CN, existing land cover, urban planning